Qualitative inquiry and research design choosing among five approaches - Creswell, John w. (SAGE Publications, 2013)
In this Third Edition of his bestselling text, John W. Creswell explores the philosophical underpinnings, history, and key elements of each of five qualitative inquiry traditions: narrative research, phenomenology, grounded theory, ethnography, and case study. In his signature writing style, the author relates research designs to each of the traditions of inquiry in a highly accessible manner. He compares theoretical frameworks, ways to employ standards of quality, and strategies for writing introductions to studies, collecting data, analyzing data, writing a narrative, and verifying results.--Publisher description